Método dos elementos finitos, análise modal e técnicas de optimização para a determinação de correspondências entre objectos - Maria Luísa Bastos (2003)
The methodology presented in this paper, for the correspondence (matching) of two images objects nodal points, was previously developed and it is based in physical modelling. In the referred methodology, the matching is done by using a local search. To overcome this disadvantage, an application of global optimization techniques in the matching process is presented in this paper. Therefore, with this solution, the objects nodes interdependence is considered. It is also presented a new solution, applicable to contour objects, developed to adequately match the excess nodes (if they exist). This situation was not possible with the usual matching